Bricolage research in history education as a scholarly mixed-methods design. Issue 1 (30th April 2019) - Sharp, Heather
Abstract : Research using a mixed-methods design is increasingly becoming the norm, crossing the myriad of educational fields of research, including history education. While commonly interpreted as a combining of qualitative and quantitative methods, mixed methods in history education can also extend to a bricolage approach, whereby the epistemological aspect of research is explicitly used to frame a study incorporating a combination of interdisciplinary methodologies and theoretical underpinnings. It extends beyond the often asserted binary of qualitative and quantitative research. In considering directions of qualitative research in the broad discipline area of education, the work of researchers such as Kincheloe (2005) and Denzin and Lincoln (2005) is used throughout this paper within a qualitative research context based on the work of Kincheloe and Tobin (2006). Adopting their approach of investigating the complexity of the lived world means placing research within a number of contexts. Research can be framed – from conceptualization to data gathering to analysis – in a range of contexts, appropriately matched between stage of research and underpinning theories. This paper reports on how bricolage can be used to frame research in history education.